PENGARUH SISTEM PENGENDALIAN MANAJEMEN DAN INOVASI TERHADAP KINERJA MANAJERIAL JASA PERHOTELAN DI KOTA MALANG - Ratnawati, Ratnawati (Manajemen & Bisnis Jurnal, 2018)
The purpose of this study was to determine the effect of Management Control Systems and innovation on the managerial performance of hospitality services in Malang. The sample used in the study was the manager of seven three-star hotels in Malang. The results showed that the management control system and innovation had an influence on the managerial performance of three-star hospitality services in Malang. These results indicate that the role of management in implementing SPM well through a clear mission and being able to communicate to all members can improve managerial performance, while innovations made through new ideas in hotel management will also improve managerial performance. Keywords: Management Control Systems, Innovation and Managerial Performance